Development of News Text Writing E-Module Designing The Concept of Differentiation for Senior High School Students - Aegustinawati Aegustinawati; Yeti Mulyati; Khaerudin Kurniawan (Jurnal Kependidikan)
This research aims to produce a product as an e-module for writing news texts with the concept of differentiation. The research method used was Research and Development (R&D) with the ADDIE model consisting of five stages, namely analysis, design, development, implementation, and evaluation. Data collection techniques were carried out through observation, interviews, questionnaires, and initial tests of news text writing ability. The data sources were teachers and students of grade XI grade XI high school. Based on the needs analysis data, the e-module was designed and developed, then validated by material experts, learning experts, media experts, and expert practitioners. The data analysis technique used quantitative and qualitative analysis. Expert validation showed that this product was "very feasible" to be used as teaching material for writing news texts with an average assessment percentage reaching 96%. The results showed that the news text writing e-module designed with the concept of differentiation proved to be effective in improving the ability of grade XI students to write news texts. This is evidenced by the significant improvement of the initial and final test results of the ability to write news texts with a significance value of <0.001 through the Wilcoxon test. The research product also received positive responses from users both in terms of students and teachers with achievement of 93% and 91% feasibility percentages respectively. It can be concluded that the news text writing e-module designed with the concept of differentiation meets the needs and expectations of users and can be used to improve the ability to write news texts for high school students.